Pharmacological read-through of R294X Mecp2 in a novel mouse model of Rett syndrome. (29th May 2020) - Merritt, Jonathan K; Collins, Bridget E; Erickson, Kirsty R; Dong, Hongwei; Neul, Jeffrey L
Abstract: Rett syndrome (RTT) is a neurodevelopmental disorder primarily caused by mutations in Methyl-CpG-binding Protein 2 ( MECP2 ). More than 35% of affected individuals have nonsense mutations in MECP2 . For these individuals, nonsense suppression has been suggested as a possible therapeutic approach. To assess the viability of this strategy, we created and characterized a mouse model with the common p.R294X mutation introduced into the endogenous Mecp2 locus ( Mecp2 R294X ) . Mecp2 R294X mice exhibit phenotypic abnormalities similar to those seen in complete null mouse models; however, these occur at a later time point consistent with the reduced phenotypic severity seen in affected individuals containing this specific mutation. The delayed onset of severe phenotypes is likely due to the presence of truncated MeCP2 in Mecp2 R294X mice. Supplying the MECP2 transgene in Mecp2 R294X mice rescued phenotypic abnormalities including early death and demonstrated that the presence of truncated MeCP2 in these mice does not interfere with wild-type MeCP2. In vitro treatment of a cell line derived from Mecp2 R294X mice with the nonsense suppression agent G418 resulted in full-length MeCP2 protein production, demonstrating feasibility of this therapeutic approach. Intraperitoneal administration of G418 in Mecp2 R294X mice was sufficient to elicit full-length MeCP2 protein expression in peripheral tissues. Finally, intracranial ventricular injection of G418 in Mecp2 R294X mice induced expression of full-length MeCP2 protein in the mouse brain. These experiments demonstrate that translational read-through drugs are able to suppress the Mecp2 p.R294X mutation in vivo and provide a proof of concept for future preclinical studies of nonsense suppression agents in RTT.